2022
DOI: 10.3389/fmicb.2022.895942
|View full text |Cite
|
Sign up to set email alerts
|

The Global Regulator CcpA of Listeria monocytogenes Confers Sensitivity to Antimicrobial Fatty Acids

Abstract: Free fatty acids (FFAs) are known to exhibit antimicrobial and anti-virulent properties against bacterial pathogens. Specific FFAs, such as lauric acid (LA; C12:0), exert both effects against the foodborne pathogen Listeria monocytogenes: at low levels, LA acts to inhibit the activity of the virulence regulator PrfA, whereas at higher levels, LA inhibits bacterial growth. Deletion of prfA is known to promote tolerance toward antimicrobial FFAs, suggesting that the response of L. monocytogenes to anti-virulent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…These results confirmed that emodin may play an antibacterial role by binding and interacting with CcpA in S. suis . Analogously, CcpA in Listeria monocytogenes was involved in the response to antimicrobial free fatty acids [74] .…”
Section: Resultsmentioning
confidence: 99%
“…These results confirmed that emodin may play an antibacterial role by binding and interacting with CcpA in S. suis . Analogously, CcpA in Listeria monocytogenes was involved in the response to antimicrobial free fatty acids [74] .…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, bacteria are capable of developing resistance against the antimicrobial activity of FFAs. Indeed, FFA-tolerant strains were readily isolated by serial passage of L. monocytogenes in broth with increasing concentrations of antimicrobial medium- and long-chain FFAs (Thomasen et al 2022a , b ). Genome sequencing of FFA-tolerant isolates revealed mutations in genes involved in glycosylation of wall teichoic acids (WTAs) (Thomasen et al 2022a ).…”
Section: Listeria Monocytogenesmentioning
confidence: 99%
“…4 ). A different subset of FFA-tolerant isolates was found to carry mutations in the ccpA gene encoding the catabolite control protein A, CcpA, a major transcriptional regulator of carbon catabolite repression in L. monocytogenes (Thomasen et al 2022b ). Inactivation of ccpA promotes growth in the presence of lauric acid (C12:0) and palmitic acid (C16:1) and results in a more hydrophilic cell surface.…”
Section: Listeria Monocytogenesmentioning
confidence: 99%
See 2 more Smart Citations